An Experimental Study on Cloth Drying by Utilizing Low Temperature Heat Source - DANANG PRIAMBODO (NIM : 13114063), MUHAMAD
Cloth drying is one of the most important daily activities and it is a sector that consumes large amount of energy. Cloth drying has become constricted to indoor drying over time due to various factors. This method is usually ineffective and takes much longer. On the other hand, a recent evaluation in the UK revealed that 63% of waste energy is a low temperature heat. Now, a special drying room that is attached to an air conditioner condenser can be designed to utilize its low temperature heat. The purpose of this research is to know the influence of temperature, air rate, and hanger width to drying rate and drying time, to know the influence of relative humidity to equilibrium moisture content and to determine the optimum condition of drying. This experiment was done by simulating cloth drying in a duct, using a fan and an electric heater. With a two-level factorial design, the selected conditions are temperatures at 26 & 40 oC, drying air rates at 0.33 & 1 m/s, and hanger widths at 1 & 5 cm. There is an additional experiment with conditions at 33 oC, 0.67 m/s, and 3 cm. From this experiment, the conclusions are the wider the hanger width, the higher the drying air rate, and the higher the temperature, the greater the drying rate would be. Temperature has the biggest effect. Nevertheless, there is an interaction between two variables, in which an interaction between temperature rise and drying air rate rise would significantly increase the constant drying rate, whereas, any interaction with hanger width rise would decrease it. The reduction of the drying airÃ‚Â’s relative humidity could generally decrease the equilibrium moisture of the cloth. The optimum conditions for this design were at 40 oC temperature, 1 m/s drying air rate, and 1 cm hanger width.